Relationship between cognitive impairment and olfactory function among older adults with olfactory impairment. Issue 3 (June 2021) - Suzuki, Hirokazu; Teranishi, Masaaki; Katayama, Naomi; Nakashima, Tsutomu; Sugiura, Saiko; Sone, Michihiko
Abstract: Objective: Understanding the relationships among aging, cognitive function, and olfaction may be useful for diagnosing olfactory decline in older adults. Olfactory function declines in the early stage of neurodegenerative diseases, including Alzheimer's and Parkinson's diseases. Aging and cognitive impairment are associated with olfactory decline. Moreover, the assessment of hyposmia and anosmia is paramount to the diagnosis of neurodegenerative diseases. We aimed to assess the relationships among aging, cognitive function, and olfaction in patients with olfactory impairment. Methods: This observational study included 141 patients with olfactory deterioration who presented with dementia, mild cognitive impairment (MCI), age-related hyposmia, or postviral olfactory dysfunction (PVOD). The patients underwent T&T olfactometry, a self-administered odor questionnaire (SAOQ), a visual analog scale (VAS), and a Mini-Mental State Examination. Results: T&T odor recognition thresholds decreased with aging ( p < 0.01) and cognitive impairment ( p  < 0.08). The average T&T recognition thresholds were 5.1, 4.6, 4.2, and 3.7 in dementia, MCI, age-related hyposmia, and PVOD, respectively. Moreover, the average differences between the detection and recognition thresholds were 3.7, 2.8, 2.3, and 2.0 in dementia, MCI, age-related hyposmia, and PVOD, respectively. Hyposmia with dementia presented the highest recognition thresholds ( p  < 0.05) and the largest differences between the T&T detection and recognition thresholds, compared with age-related hyposmia and PVOD ( p  < 0.05). Hyposmia with dementia had the highest SAOQ and VAS scores compared with the other groups ( p  < 0.05). Conclusion: The possibility of dementia should be investigated in patients with hyposmia, including those with high T&T recognition thresholds, a large difference between the T&T detection and recognition thresholds, and high SAOQ and VAS scores.